NILAI BUDAYA DALAM PERIBAHASA JEPANG - Trahutann, Sri Wahyu Istana (Fakultas Ilmu Budaya Universitas Diponegoro, 2013)
Universally every language in the -world has proverbs. Proverb is one of language elements that inclines to be steady and not experiencing a change both from structure and meaning sides. Proverb is inherited hereditary. Proverb contains social wisdom of the owner. Not only that, proverb also becomes guidance to do and has a long lasting endurance. In the other worlds, Japanese proverbs are used to comm unicate every cultural elements that Japanese has.